Evaluating vocational education policy in a disadvantaged region: Evidence from a CIPP-based study - Anik Ghufron; Septian Rahman Hakim; Dafid Slamet Setiana; Gumpanat Boriboon; Aris Dianto (Jurnal Pendidikan Vokasi, 2025)
This study evaluates the performance of vocational education policy at SMK Maharati, a vocational high school located in a disadvantaged (3T: frontier, outermost, and underdeveloped) region of Indonesia, using the Context–Input–Process–Product (CIPP) evaluation model. This study employed an evaluative mixed-methods approach and analyzed secondary data from four institutional stakeholder satisfaction reports involving educators, educational staff, students, parents, and industry partners (IDUKA) during the 2024/2025 academic year. Quantitative data were analyzed using descriptive statistics, one-sample t-tests, Pearson correlation analysis, and regression analysis, while qualitative data were analyzed using thematic content analysis. The findings reveal a clear dichotomy between external and internal stakeholder satisfaction. Parents, students, and industry partners consistently reported high levels of satisfaction, particularly regarding student character, work ethic, and industry-relevant competencies. In contrast, educators and educational staff reported only moderate levels of satisfaction, with compensation and workload emerging as the primary sources of dissatisfaction. Statistical analysis confirmed a significant negative relationship between perceived workload and salary satisfaction, indicating structural weaknesses in human resource management. The study concluded that vocational education policy at SMK Maharati is externally effective yet internally fragile, relying heavily on the goodwill of educators rather than sustainable institutional systems. Integrated reforms in human resource management, workload management, and internal coordination are essential to ensure long-term sustainability of vocational education quality in disadvantaged regions.